Inovasi Manajemen K3 Laboratorium Pendidikan Tinggi - Ariel Natanael Rengkuan (Lembaga Pengembangan Kinerja Dosen, 2025)
Occupational Safety and Health (K3) in university laboratories is a crucial factor in ensuring the smooth running of education, research, and service activities. This research aims to identify and evaluate the K3 management innovations that have been implemented in university laboratories in the last decade to reduce the risk of accidents and build a sustainable safety culture. The methodology used was a systematic literature review of 50 publications for the period 2015–2025, with data sources from Google Scholar, Web of Science, and Scopus indexed journals. The thematic analysis groups innovation into three main categories: digital technology, procedural innovation, and safety culture. The results show that digital technologies such as the Internet of Things, K3 dashboards, and inspection applications can reduce the number of accidents by up to 27%. Procedural innovations, including digital checklists and adaptive SOPs, increased compliance by 35%, while a safety culture based on gamification training and online campaigns increased awareness by up to 40%. These findings confirm that an integrated approach between technology, procedures, and culture provides the most optimal results. This study contributes to the development of an integrated K3 management model and opens up opportunities for further research related to the application of artificial intelligence in laboratory safety systems